Feasibility of laparoscopic liver lobectomy in dogs. (11th February 2021) - Michael, Aleisha E.; Case, J. Brad; Massari, Federico; Giuffrida, Michelle A.; Mayhew, Philipp D.; Carvajal, Jose L.; Regier, Penny J.; Runge, Jeffrey J.; Singh, Ameet
Abstract: Objective: To determine the feasibility of laparoscopic liver lobectomy (LLL) in dogs by using canine cadavers and to describe the clinical application in dogs with liver disease. Study design: Ex vivo experiment and descriptive case series. Sample population: Twelve canine cadavers and six client‐owned dogs. Methods: Cadavers underwent LLL with an endoscopic stapler. The percentage of liver lobe resected was determined by volume. The distance from the staple line to hilus was measured. Medical records of dogs undergoing LLL were reviewed. Results: In cadavers ≤15 kg, left lateral lobectomy completeness was 87.3% (84.6%–96.6%), and remaining median (interquartile range) hilar length was 1 cm (0.25‐1.75). Left medial lobectomy completeness was 72.5% (66.7%–80%), and remaining hilar length was 1.6 cm (0.47‐1.75). Central division resection completeness was 68.3% (60%–92.9%), and remaining hilar length was 2.7 cm (0.8‐5). Laparoscopic liver lobectomy was not feasible for right division lobes and in cadavers >15 kg. Five dogs with peripheral quadrate or left lateral lobe masses underwent stapled, partial laparoscopic lobectomy (30%–90%). One dog underwent stapled, left lateral lobectomy (90%) after open procedure conversion. Histopathological diagnoses included hepatocellular carcinoma (3), nodular hyperplasia (1), biliary cyst adenoma (1), and fibrosis (1). Conclusion: Laparoscopic liver lobectomy of the left and central divisions is feasible in cadavers ≤15 kg with an endoscopic stapler. Partial LLL of the left and central divisions is feasible in select dogs with liver disease. Clinical significance: Laparoscopic liver lobectomy may be a viable alternative to laparotomy in small‐to‐medium size dogs with peripheral liver masses of the left and central divisions.